(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research deals with the crime of maritime piracy and its impact on both maritime safety and international maritime commercial transport operations maritime safety and international maritime commercial transport operations, it has significant repercussions on the security of maritime navigation. The research reviews the definition and definition of maritime piracy in general, From the point of view of international jurisprudence, with reference to the definitions of the most important international conventions, especially the United Nations Convention The United Nations Law of the Sea for the year 1982 in particular, in addition to shedding light on the elements and types of this crime, wit A review of the most important reasons and factors that helped the emergence, spread and exacerbation of the crime of maritime piracy, especially in The twenty-first century. The research also focuses on the efforts made by countries in combating the crime of maritime piracy to reduce them and prevent their spread,in addition to addressing the effects of this crime and its repercussions. The research reached many results: • The seriousness of the maritime piracy crime as it dates back to ancient time • The inadequacy of international conventions, especially the United Nations Convention on the Law of the Sea of ​​1982, in developing a comprehensive definition of all acts of maritime violence